2021
DOI: 10.1182/blood-2021-149638
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Anti-CD-19 Chimeric Antigen Receptor T-Cell Therapy in the Older Population with Diffuse Large B Cell Lymphoma: A Meta-Analysis

Abstract: Introduction Patients with refractory or relapsed diffuse large B cell lymphoma (DLBCL) have very limited treatment options. Axicabtagene ciloleucel, tisagenlecleucel, and lisocabtagene maraleucel are the Anti-CD-19 chimeric antigen receptor T-cell (CAR-T) therapy have been recently approved for refractory or relapsed DLBCL patients who have failed at least two lines of treatment. CAR-T therapy has significant adverse effects, most notably cytokine release syndrome (CRS) and immune effector cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Overall, toxicity in patients ≥65 years was manageable, despite elevation in some proinflammatory and immune-modulatory cytokines and chemokines, which are known to be associated with grade ≥3 toxicities ( 9, 38 ). Therefore, although a recent meta-analysis demonstrated that older patients are at a higher risk of immune effector cell–associated neurotoxicity syndrome compared with younger patients ( 39 ), the safety profile of axi-cel in this prospective randomized trial demonstrates that toxicities associated with neurologic events are manageable and that interventions that aim to minimize higher-grade toxicity for this patient population are effective.…”
Section: Discussionmentioning
confidence: 83%
“…Overall, toxicity in patients ≥65 years was manageable, despite elevation in some proinflammatory and immune-modulatory cytokines and chemokines, which are known to be associated with grade ≥3 toxicities ( 9, 38 ). Therefore, although a recent meta-analysis demonstrated that older patients are at a higher risk of immune effector cell–associated neurotoxicity syndrome compared with younger patients ( 39 ), the safety profile of axi-cel in this prospective randomized trial demonstrates that toxicities associated with neurologic events are manageable and that interventions that aim to minimize higher-grade toxicity for this patient population are effective.…”
Section: Discussionmentioning
confidence: 83%
“…Overall, toxicity in patients ≥65 years was manageable, despite elevation in some proinflammatory and immune-modulatory cytokines and chemokines, which are known to be associated with grade ≥3 toxicities (9,38). Therefore, although a recent meta-analysis demonstrated that older patients are at a higher risk of immune effector cellassociated neurotoxicity syndrome compared with younger patients (39), the safety profile of axi-cel in this prospective randomized trial demonstrates that toxicities associated with neurologic events are manageable and that interventions that aim to minimize highergrade toxicity for this patient population are effective.…”
Section: Discussionmentioning
confidence: 99%